Limit theorems for the number of crossings of a fixed plane by certain sequences of generalized dbffusion processes - Goshko, L. V.; Portenko, N. I.; Гошко, Л. В.; Портенко, М. І. (Institute of Mathematics, NAS of Ukraine, 1994)
We characterize the weak convergence of certain sequences of generalized diffusion processes by using a specific functional of a process, namely, the number of crossings of a fixed plane by this process.